Vehicle Electro-Mechanical Brake System: A Mechatronic Application - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2009)
An electro-mechanic brake system, which has the potentiality to be used in future cars, has been studied and a prototype of the brake system has been produced. The electro-mechanic brake system has different working principles then hydraulic brake system. Hydraulic force or air pressure is used to obtain the braking force on the wheels in the hydraulic braking systems, whereas a solenoid valve push force is used to stop the car in electro-mechanic systems. A censor controlled the RPM of the wheel and the data was passed to a micro controller and micro controller produced PWM signals according to obtained signal. Thus, push force of the solenoid valve was controlled by micro controlled according to the braking ratio. If the wheel slows down the turning speed, then micro controller stops to sending PWM signals and solenoid is relaxed until wheels turns again. This cycle continues until the all wheels are stopped. A prototype of the system has been constructed and tested. The initial results indicated that the system can be potentially used in the automotives.
Keywords: electro-mechanic brake system; ABS; solenoid valve control; automotive mechatronics; mechatronics education